Epidemiological study of hypertensive retinopathy in the primary care setting: Retrospective cross-sectional review of retinal photographs. Issue 4 (1st December 2016) - Chiang, Lap-kin; Yau, Michael K.C.; Kam, Cheuk-wai; Ng, Lorna V.; Zee, Benny C.Y.
Abstract : Objective: The objective is to estimate the prevalence and grading of hypertensive retinopathy in the primary care setting; examine the patient characteristics associated with hypertensive retinopathy; and examine the association of hypertensive retinopathy and other hypertension complications. Methods: This is a retrospective cross-sectional study. Subjects included adult hypertensive patients with available and gradable retinal photographs. Results: Two hundred fifty-six male hypertensive patients (34.3%) and 491 female hypertensive patients (65.7%) were included. The average duration of hypertension was 7.2 years, and 49.8% and 41.2% of patients were taking one or two antihypertensive medications respectively. Among 1491 qualified retinal photographs (744 right eye and 747 left eye), 24.9%, 62.6%, and 12.5% were classified as showing normal, mild, and moderate hypertensive retinopathy respectively. The three commonest retinal signs were generalized or focal arteriolar narrowing (650 cases, 43.6%), hard exudates (168 cases, 11.3%), and opacity (copper or silver wiring) of the arteriolar wall (166 cases, 11.1%). Patients older than 61 years, having hypertension for more than 15 years, or taking three or more antihypertensive medications were significantly associated with hypertensive retinopathy ( P <0.05). Conclusion: In a primary care clinic in Hong Kong, 77.1% of hypertensive patients had hypertensive retinopathy. Advanced hypertensive retinopathy was the commonest target organ damage for hypertensive patients in a primary care clinic.